(untitled) (Anclajes, 2021)
I review the development of studies on the nineteenth century in literary criticism in Argentina from the first twenty-five volumes of Anclajes. These studies achieved a strong imprint and visibility during the 1990s and mid-1990s; to suffer, later, a notorious stagnation. The shift in these interests seems to be almost a foreseeable consequence given the enormous influx of critical approaches focused on the situation of the most recent Latin American literature.